2005
DOI: 10.1038/sj.emboj.7600886
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the entire cytoplasmic portion of a sensor histidine-kinase protein

Abstract: The large majority of histidine kinases (HKs) are multifunctional enzymes having autokinase, phosphotransfer and phosphatase activities, and most of these are transmembrane sensor proteins. Sensor HKs possess conserved cytoplasmic phosphorylation and ATP-binding kinase domains. The different enzymatic activities require participation by one or both of these domains, implying the need for different conformational states. The catalytic domains are linked to the membrane through a coiledcoil segment that sometime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
341
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 273 publications
(367 citation statements)
references
References 53 publications
15
341
0
2
Order By: Relevance
“…The residues corresponding to Pro-410 and Phe-436 in the histidine kinase TM0853 from Thermotoga maritima lie in the first and second alpha-helices of the DHp domain and share contacts with residues in the hydrophobic core of the DHp domain (Marina et al, 2005). We consequently asked if KinA carrying both the P410L and F436S substitutions would have a lower affinity for Sda than the single mutant proteins.…”
Section: The Replacement Of Phe-436 With Serine Increases the Activitmentioning
confidence: 99%
See 4 more Smart Citations
“…The residues corresponding to Pro-410 and Phe-436 in the histidine kinase TM0853 from Thermotoga maritima lie in the first and second alpha-helices of the DHp domain and share contacts with residues in the hydrophobic core of the DHp domain (Marina et al, 2005). We consequently asked if KinA carrying both the P410L and F436S substitutions would have a lower affinity for Sda than the single mutant proteins.…”
Section: The Replacement Of Phe-436 With Serine Increases the Activitmentioning
confidence: 99%
“…Based on a sequence alignment of KinA with the TM0853 histidine kinase from T. maritima for which a high-resolution X-ray structure is available (Marina et al, 2005), we found that the T. maritima residues corresponding to Ala-413 and Tyr-431 are also surface exposed and lie very close to each other on the same face of the DHp domain as the conserved histidine corresponding to KinA His-405, the site of autophosphorylation (Fig. 6).…”
Section: Sda Binding Decreases the Solvent Accessibility Of Residues mentioning
confidence: 99%
See 3 more Smart Citations